Relevansi Pemeringkatan Kata Kunci Dengan Menggunakan Dalil Zipf Pada Abstrak Skripsi Hukum Perdata Fakultas Hukum Universitas Sriwijaya Tahun 2018-2022 - Vitriana, Novita; Ria Febrianti, Beta; Tiara Hilda Safitri, Rts (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to see the relevance of the results of subject indexing through the zipf argument with thesis keywords in several thesis abstracts for the Civil Law Department, Faculty of Law, Sriwijaya University 2018-2022 and also to find out the topic of the thesis. This research uses a quantitative descriptive approach with a bibliometric measurement method using the zipf theorem. The object is the undergraduate student thesis of the Department of Civil Law, Faculty of Law, University of Sriwijaya from 2018 to 2022 as many as 60 thesis abstracts. The research sample is the entire research object. The results of the research apply the use of the zipf argument as a method for determining keywords in the thesis abstracts of the civil law study program, Faculty of Law, Sriwijaya University, 2018-2022. Keywords as a result of zipf ranking are then compared with the author's keywords to obtain the level of relevance of these keywords. From the calculation of the relevance, it can be said that indexing through Zipf's law shows a high level of marginal relevance when equated with the relevant level and irrelevant index results. The proof is through estimatio